Correlation between colonoscopy difficulty and personality traits: study protocol for a prospective, observational, multicentre study - Dong Wu; Yinan Jiang; Duan Wang; Ruihong Zhao; Shengyu Zhang; Yutang Ren; Dayu Kuai (BMJ Open)
Background Colonoscopy is widely used for screening and treatment of early colonic lesions and is critical for the early diagnosis of colorectal cancer. However, due to its invasive nature, colonoscopy can cause pain and discomfort for patients and is often associated with prolonged insertion times or failed attempts. Difficult colonoscopy is characterised by a caecal insertion time greater than 10 min, multiple insertion attempts or failed insertion, with an incidence rate of approximately 25%. Studies have shown that objective factors such as gender, age, body mass index, bowel preparation quality and history of abdominal or pelvic surgery can make colonoscopy difficult. Integrating clinical evidence and the established impact of personality traits on certain gastrointestinal conditions, a patient’s personality traits and emotional and psychological states may also influence caecal insertion time during colonoscopy. Currently, no studies have investigated the predictive role of patients’ personality on the difficulty of colonoscopy. This study used the Chinese-Language 44-Item Big Five Personality Inventory to assess patients' personality traits, aiming to observe whether there is a correlation between the degree of difficulty of colonoscopy and any of the personality traits.Methods and analysis This is a prospective, observational, multicentre study. Patients undergoing colonoscopy will be required to complete the Big Five Inventory, the General Anxiety Disorder 7-item scale and the Patient Health Questionnaire 9-item Depression Scale before colonoscopy. During the colonoscopy, the endoscopist will record the primary endpoint of caecal insertion time. The Boston Bowel Preparation Scale, patients pain scores and willingness to undergo a subsequent colonoscopy will be recorded as the secondary endpoints. The study plans to enrol a total of 322 patients. Survival analysis will be used to examine the correlation between colonoscopy difficulty and the Big Five personality traits.Ethics and dissemination This study was approved by the Ethics Committee of the Peking Union Medical College Hospital (No. K2128). All participants in this study will provide written informed consent. The results of this study will be published in an open-access way. There is no independent data monitoring committee because this is an observational and low-risk study.Trial registration number NCT05584423.